Comparative analysis of leading and lagging techniques in investment strategies - Detri Heri Gemita; Muchriana Muchran; Mira Mira (Optimum: Jurnal Ekonomi dan Pembangunan, 2026)
This research compares the accuracy and performance of leading and lagging indicators in predicting stock price movements on the IDXGrowth30 index over a three-year period from January 2021 to December 2023. Leading indicators provide signals before a trend forms, while lagging indicators confirm trends after price movements have occurred. The Relative Strength Index (RSI) is used as a representation of the leading indicator, while the Parabolic Stop and Reverse (Parabolic SAR) represents the lagging indicator. This study evaluates the effectiveness of technical indicators in supporting investment decisions based on signaling theory. The results show that RSI has an accuracy rate of 94%, higher than Parabolic SAR's 39%, and also generates a larger return (14.652 compared to 3.032). These findings indicate that RSI is more effective in providing fast and accurate signals for growth-oriented stocks. This research fills a gap in the literature regarding the comparison of technical indicators on the IDXGrowth30 index, although the generalization of results remains limited.